1979
DOI: 10.1021/j100480a010
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity in surfactant solutions. Characteristics of the micellar aggregates and the formation of periodic colloidal structures

Abstract: Publicatlon costs assisted by the University of LundThe properties of viscoelastic dilute aqueous solutions containing the hexadecyltrimethylammonium cation (CTA+) are investigated by monitoring the proton magnetic resonance spectrum and the linear dichroism induced in a shear gradient. It is found that the viscoelastic behavior of the dilute solutions correlates with the formation of rod-shaped micellar aggregates. This correlation is manifested both with respect to changes in composition and in temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

1981
1981
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 10 publications
2
76
0
2
Order By: Relevance
“…One intriguing result was that the viscoelasticity of the solution began to increase well below the cmc of the surfactant. Some years later, Gravsholt and coworkers recognized that other types of additives, such as salicylate or chlorobenzoate counterions, are actually solubilized by the micelles, lowering the cmc of the surfactant [59,125]. It was suggested by the same authors that the viscoelasticity had the same physical origin as that of polymer solutions and melts, namely entanglements and reptation [104].…”
Section: Linear Rheology and Scalingmentioning
confidence: 99%
“…One intriguing result was that the viscoelasticity of the solution began to increase well below the cmc of the surfactant. Some years later, Gravsholt and coworkers recognized that other types of additives, such as salicylate or chlorobenzoate counterions, are actually solubilized by the micelles, lowering the cmc of the surfactant [59,125]. It was suggested by the same authors that the viscoelasticity had the same physical origin as that of polymer solutions and melts, namely entanglements and reptation [104].…”
Section: Linear Rheology and Scalingmentioning
confidence: 99%
“…On the other hand, a low-viscosity micelle solution sometimes transforms into a highly viscous solution when a certain aromatic compound, for example the salicylate ion, is added. [1] Transmission electron microscope (TEM) pictures reveal that the viscous solutions contain rodlike structures.…”
Section: Formation Of Giant Liposomes From Crystalline Complexes Of Mmentioning
confidence: 99%
“…Therefore, the suggestion that viscoelastic solutions contain linked spherical micelles is not likely. Ulmius et al (37) suggested that the properties of these solutions are caused by a periodic colloidal structure, formed as a result of the repulsive force between the aggregates. Fuhrop and Helfrich (38) proposed that helical ribbons are formed when cetyltrimethylammonium bromide and salicylic acid are dissolved in water.…”
Section: Counterions Which Are Able To Induce Viscoelasticity In Surfmentioning
confidence: 99%